Go green with WEEE: Eco-friendly approach for handling e-waste - Jaiswal A.; Samuel C.; Patel B.S.; Kumar M. (My University, 2025)
The rate of EEE put in market and WEEE generated in previous years defines the magnitude of the problem of e-waste handling. Many researches have indicated the potential threat of e-waste and stated the need of proper recycling strategies and global ewaste management policies to confront the growing problem. This study discusses the awareness in people for handling obsolete electronic products and suggests a green framework for e-waste. The study also discusses the role of EPR for e-waste handling, defining the need of green manufacturing and its approaches which can lead to solutions for WEEE. © 2015 The Authors.